Navigating the Social Landscape: Challenges Faced by Artists in Manipur - Dr Gurumayum Bijoykumar Sharma (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
If there be a society, it has its own rules and regulations. The rules and regulations control the people living in the society as peg in wooden structure. However, if some liberties are not given to the artists, they won’t be able to be successful artists. They need enough time to indulge and to craze in their desired lines or subject. In other words, there must be time in which they can indulged or craze. When his or her indulgence disturbs the social norms, one must know his or her behaviour very well. It is not an easy task to do art. When they endeavour forgetting- eating, drinking and sleeping, they must be praised and encouraged instead of thinking then as mad or duty less. Fearing the norms of society, sometimes some artists devoted their lives to art, happen to remain unmarried throughout their lives. Artists are human beings. They have hearts and souls. Because of devotion to arts, artists sometimes have their loved ones- parents or friends; however, keeping life and death behind the screen, they spread the glory of this land in India and outside India. We need ponder this. This article aims at showing the shortcomings and disadvantages met by artists by observing internally and externally, starting from the schooling system. Again, main object of this article is to produce the measure to lesser the shortcomings, by analysing them one by one.